Anti-lawyers : religion and the critics of law and state - Saunders, David, 1940- (Routledge, 1997)
Anti-Lawyers discusses how we should regard today's critics of law and government in the light of the historical still unfinished struggle to separate the legal regulation of civil life from the Christian regulation of conscience.